(untitled) (The Research of Medical Science Review, 2025)
Background: Asthma is a leading chronic respiratory illness among children, significantly affecting their daily functioning and quality of life. Effective management protocols, including pharmacologic treatment, inhaler technique training, and follow-up care, are essential for achieving optimal control and improving outcomes. Objective: To evaluate the effectiveness of current asthma management protocols in pediatric patients by analyzing changes in symptom control and quality of life. Methods: This longitudinal observational study was conducted at Mother and Children complex DHQ Sheikhupura, during May 2024 to December 2024. This study included 107 pediatric asthma patients. Baseline data on demographics, asthma severity, management adherence, and quality of life were collected and compared to follow-up data at 6 months using the Asthma Control Test (ACT) and Results: Among 107 pediatric asthma patients, significant improvements were observed over six months. ACT scores increased from 16.3 ± 4.1 to 21.5 ± 3.2 (p < 0.001), while nighttime symptoms and school absences decreased by more than 50% (p < 0.001). Quality of life scores across symptoms, activity, and emotional domains also improved significantly (p < 0.001). High adherence to medication and follow-up protocols was associated with better outcomes. Conclusion: Current asthma management protocols significantly improve symptom control and quality of life in pediatric patients over six months. Emphasizing adherence, education, and routine follow- ups remains critical for sustained asthma control.